Analysis of S1 DRG Programming to Determine Location of the DRG and Ideal Anatomic Positioning of the Electrode. Issue 2 (2nd September 2019) - Falowski, Steven M.; Conti, Keith R.; Mogilner, Alon Y.
Abstract : Introduction: Dorsal root ganglion (DRG) stimulation has been established as a therapy in the treatment of chronic pain. Ideal electrode placement is guided by proper identification of the location of the DRG. The location of the S1 DRG is not well delineated and can be variable making ideal location of the electrode placement difficult based on fluoroscopic imaging. Methods: This is a retrospective analysis of postoperative programming of S1 DRG leading across two centers. There were 34 lead placements in 24 patients included in this study. Programming parameters and contacts used were evaluated based on the position of the electrode in reference to the sacral border. Results: The majority of the patient programming parameters were recorded at six weeks following the implant. Most commonly, the programming used a simple continuous bipole configuration. Of the 34 leads programmed, 17 (50%) had programming on the sacral border, 14 (41%) were considered posterior, and 3 (9%) were anterior to the sacral border. Conclusion: This analysis of S1 DRG programming demonstrates that ideal positioning of the majority of the contacts for the electrode should be posterior and along the sacral border on fluoroscopic imaging. These findings also suggest that the S1 DRG may be located most reproducibly at the border of the intraforaminal and intracanalicular region.